KORELASI ANTARA KEPEDULIAN ORANG TUA DENGAN KUALITAS PERTEMANAN REMAJA DI SMP N 10 TAKENGON - Ipak Rima Tuah Niate; Abu Bakar; Said Nurdin (JIMBK: Jurnal Ilmiah Mahasiswa Bimbingan & Konseling, 2017)
Keywords: Concern Parents, Teens Friendship QualityParents who care about their friendship would seek in such a way that the children can have a good friend in the neighborhood. This study seeks to describe the correlation between the awareness of parents with teenage friendship quality in SMP N 10 Takengon. This study aims to determine the existence of a significant relationship between the awareness of parents with teenage friendship quality. The population in this study are students of SMP N 10 Takengon totaling 120 people. The sampling technique in this research is nonprobability sampling. This study is a quantitative study with descriptive and correlational. The data collection is done by spreading the questionnaire instrument. Those items which are responded by survey respondents in the answers to the five categories. The data were processed and analyzed using SPSS. The results showed that the awareness of parents in SMP N 10 Takengon in general are in the medium category, while the quality of adolescent friendships in middle category. Data analysis technique used in the study to be missed formulation number 1 and 2 is a descriptive analysis of the percentage, whereas for the formulation of the problem number 3 using Product Moment correlation test. The results of data analysis using correlation there is a significant correlation between the awareness of parents with teenage friendship quality are obtained r_xy, that there is a significant correlation between the awareness of parents with teenage friendship quality. Thus the higher the awareness of parents, the better the quality of friendship with the child in SMP N 10 Takengon. Some suggestions are recommended